2019
DOI: 10.1186/s12957-019-1612-x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection for gastric ectopic pancreas: a single-center experience

Abstract: Background and objective Endoscopic submucosal dissection (ESD) is a minimal invasive technology and could allow “en bloc” resection for superficial gastric tumors. The aim of this study is to evaluate the safety and feasibility of ESD for gastric ectopic pancreas (EP). Methods A total of 93 patients diagnosed with ectopic pancreas who underwent ESD between January 2011 and June 2017 were enrolled. The demographic, clinical, and endoscopic data were collected and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…However, developed countries such as South Korea and Japan are more inclined to ESD and EMR, while for developing countries in Southeast Asia and China, radical surgery is a more common choice. This phenomenon may be due to the inevitable bleeding complications and residual tumor in gastrointestinal endoscopy in developing countries [ 28 ]. At the same time, these surgeons always choose radical resection of GC to avoid early occurrence of metastasis because it is difficult to find micrometastases by general imaging examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, developed countries such as South Korea and Japan are more inclined to ESD and EMR, while for developing countries in Southeast Asia and China, radical surgery is a more common choice. This phenomenon may be due to the inevitable bleeding complications and residual tumor in gastrointestinal endoscopy in developing countries [ 28 ]. At the same time, these surgeons always choose radical resection of GC to avoid early occurrence of metastasis because it is difficult to find micrometastases by general imaging examination.…”
Section: Discussionmentioning
confidence: 99%
“…is phenomenon may be due to the inevitable bleeding complications and residual tumor in gastrointestinal endoscopy in developing countries [28]. At the same time, these surgeons always choose radical resection of GC to avoid early occurrence of metastasis because it is difficult to find micrometastases by general imaging examination.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we identified 158 cases of local endoscopic resection in our series. The largest series was published by Zhou et al [ 6 ] who reported endoscopic submucosal dissection in 78 symptomatic patients with good results. In this series, the majority of patients had lesions located in the submucosa or lamina propria and were less than 1cm in size.…”
Section: Discussionmentioning
confidence: 99%
“…Though ectopic pancreatic tissue presented in 37% of gastric duplication cysts, the size of ectopic pancreas reported in previous literatures is generally microscopic [ 4 ]. Zhou et al [ 5 ] demonstrated that the three common characteristics to help identify gastric ectopic pancreas including the site in the gastric antrum, central umbilication, and the complete mucous membrane. Ectopic pancreas may lead to pancreatitis with pseudocyst, and can present as a cystic mass [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced CT scan typically demonstrates gastric duplication cyst as a thick-walled cystic lesion with enhancement of the inner lining [ 3 ]. However, CT seems to be not very helpful in the diagnosis of gastric ectopic pancreas [ 5 ]. EUS could provide useful information regarding tumor size, layer of origin and echogenicity.…”
Section: Discussionmentioning
confidence: 99%